2015
DOI: 10.1111/papt.12051
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of what service users value about early intervention in psychosis services

Abstract: Service users reported that four main components of Early Intervention in Psychosis Services were helpful to them. These included a strong and effective therapeutic relationship, as well as medication, psychological therapies, and practical help and support. Services are valued both for the quality of the therapeutic relationship but also for their ability to deliver meaningful and valued treatments in this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…Three key themes were identified; 'Consistency and Communication', 'Normalising and Validating', and 'Pushing Boundaries'. All themes emphasised the importance of the relationships with either the EIP service staff or fellow SUs, which replicated the findings from previous research into the experience of EIP service users (Lester, et al, 2011;Harris, et al, 2012;Barr, Ormrod, & Dudley, 2015). To the best of the authors' knowledge, this is the first EIP service evaluation to suggest, from the perspective of SUs, the potential value of taking a graded approach to building trust and pushing boundaries through activities and peer support in EIP services.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Three key themes were identified; 'Consistency and Communication', 'Normalising and Validating', and 'Pushing Boundaries'. All themes emphasised the importance of the relationships with either the EIP service staff or fellow SUs, which replicated the findings from previous research into the experience of EIP service users (Lester, et al, 2011;Harris, et al, 2012;Barr, Ormrod, & Dudley, 2015). To the best of the authors' knowledge, this is the first EIP service evaluation to suggest, from the perspective of SUs, the potential value of taking a graded approach to building trust and pushing boundaries through activities and peer support in EIP services.…”
Section: Discussionsupporting
confidence: 72%
“…Participants also reported that the EIPS helped to support their sense of agency through a process of accepting their experiences, taking control of their care and developing a more positive sense of self. Barr et al (2015) used Q-Methodology to investigate what SUs found most valuable about EIPSs and identified four key factors: the therapeutic relationship, medical care, psychological interventions and support, coping and recovery. Relationships with EIPS workers were again identified as the most valued aspect of the service, with active listening, empathic validation and consistency of care named as key aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosis is a multifaceted experience that is characterised by a loss of touch with reality and it encompasses positive, negative and depressive symptoms (Sax et al, 1996). Psychosis is often a distressing and a debilitating experience (Barr, Ormrod & Dudley, 2015) that impacts on a person's self-concept, confidence, hopes (Connell et al, 2015) self-esteem, social roles (Braehler & Schwannauer, 2012) and it can result in a feeling of having lost oneself (Lester et al, 2011).…”
Section: Psychosis Subjective Wellbeing and Strength-based Ppismentioning
confidence: 99%
“…youth-friendliness, informality, genuineness, and flexibility tailored to individual needs which facilitated engagement (Byrne and Morrison, 2014;Barr et al, 2015;Lester et al, 2011;Uttinger et al, 2018); when opening-up, being listened to and receiving empathic non-judgemental responses (Byrne and Morrison, 2014;Barr et al, 2015;Uttinger et al, 2018). Users valued working collaboratively with HCPs (Byrne and Morrison, 2010;Harris et al, 2012) and consistency in seeing the same person regularly, having HCPs sticking with them when things were difficult (Barr et al, 2015) and building a long-term relationship with one person with whom they could talk freely, and feel understood, which facilitated engagement (Byrne and Morrison, 2014;Lester et al, 2011). When this was compromised, users reported disruption in having to repeat things to various HCPs, which affected the ability to build trust (Lester et al, 2011;Uttinger et al, 2018).…”
Section: Therapeutic Relationshipsmentioning
confidence: 99%